Navigasi robot bergerak berdasarkan landmark garis menggunakan kontroler Braitenberg dan pengolahan citra - Ali Rizal Chaidir; Gamma Aditya Rahardi; Khairul Anam (Jurnal Teknologi dan Sistem Komputer, 2020)
Line following and lane tracking are robotic navigation techniques that use lines as a guide. The techniques can be applied to mobile robots in the industry. This research applied the Braitenberg controller and image processing to control and obtain line information around the mobile robot. The robot was implemented using Arduino Uno as a controller. A webcam was connected to a computer that performs image processing using canny edge detection and sends the data to the robot controller via serial communication. The robot can navigate on the side of the line, and the success rate of the system is 100 % at a turn of 135 ° and 80 % at a turn of 90 °.